OPTIMISATION CEMENT CONTENT FOR GRAVELLY LATÉRITIC FOR REALIZATION OF PAVEMENTS BASE IN NORTH BENIN - GIBIGAYE, ADAM MOHAMED; ZEVOUNOU, CRÉPIN; ALLOBA, IDELPHONSE EZÉCHIEL (My University, 2013)
In some countries and especially in Benin, some premature fissuring of semi-rigid structures in gravelly lateritic built, for the most, with important investment costs is often established. This is mostly due to the bad proportion in binding agent and sometimes to an overexploitation of the piece of work. The present study enters within the general context of the research of alternative solutions for an efficient exploitation of local materials (gravelly) in road technique in Benin. This work has consisted to do two borrowing in each one of two zones on which a complete identification has been realized. The materials had afterwards ameliorated at 2%, 3% and 4% of cement in sight of the determination of optimal dose in cement which guarantees satisfactory mechanic characteristics. Accorded to this approach, it was determined that the using of these materials at the natural condition is possible only in sub base course. The formulation study of heterogeneous gravelly-cement in base course has revealed optimal dose relative to every borrowing. Therefore, for security reasons depended on loss of yard, all these values have been brought back at 3.5% at the implementing of gravelly-cement within study zones. The application of this study will guarantee then relative economy no less important.
Keywords: Gravelly lateritic; road; pavements; mechanic characteristics